Transnational corporations, financialization and community development in West African cocoa. (22nd October 2020) - Amanor, Kojo S
Abstract: This article examines the role of financial capital in the cocoa industry of Côte d'Ivoire and Ghana. It argues that the processes of structural adjustment in the 1980s and 1990s brought two important elements into play. Firstly, transnational corporations taking advantage of the opening of global markets to gain control over the cocoa sector, and secondly, financial institutions promoting 'country platforms' that encouraged public–private partnerships to mobilize foreign investments and define development objectives. This has led to a distinct pattern of investment, which is intimately connected with governance reforms underpinned by a diverse set of public and private alliances at different levels. The article traces these alliances which have given rise to community development programmes. However, these programmes are underpinned by a drive towards greater intensification of production through the use of inputs supported by credit, which threatens to entangle farmers in debt and lock them into the poverty inherent in the cocoa industry.